Addition of Probiotics to Feed on the Growth and Survival of Tilapia Fish Seeds - Samliok Ndobe; Andi Heryanti Rukka; Rusdin; Nanang Rahmayanti (LPPM Universitas Tadulako, 2023)
Introduction: Tilapia (Oreochromis niloticus) is one of the leading commodities of freshwater aquaculture in Indonesia. The problem that is often experienced by farmers is the absorption of fish feed nutrients that are less than optimal, due to the low quality of feed raw materials. The study aims to determine the effect of adding probiotics to feed on growth and survival, in tilapia (O. Niloticus) fry. Method: The test organisms used in this study were tilapia (O. niloticus) as many as 200 fish with an initial weight of 1.09-1.28 g/head. Tilapia seeds were obtained from UPR Saluyu, Dolo sub-district, Sigi district, Central Sulawesi. The design used was a complete randomized design (CRD). Results and Discussion: Variables observed were daily weight growth rate (LPBH), absolute weight growth (PBM), survival rate, feed conversion ratio (CTR), and water quality. Conclusion: The results showed that the highest absolute weight growth in tilapia was found in treatment D (8 mL probiotics) which was 2.04 g, the specific growth rate was (2.86% / day), and the feed conversion ratio produced (1.57), while the survival rate of tilapia obtained during maintenance was (80.00-84.00%).